Role of hepatocyte growth factor in the development of dendritic cells from CD34+ bone marrow cells - (:unkn) unknown (My University, 2000)
Background and Objectives. Hepatocyte growth factor (HGF) is known to augment the affects of stem cell factor, interleukin-3, granulocyte- macrophage colony-stimulating factor (GM-CSF), erythropoetin, and granulocyte colony-stimulating factor, all of which are involved in hematopoiesis. HGF is also known to have a role in immune responses. The aim of this study was to investigate whether HGF is involved in the development of dendritic cells (DC) from CD34 bone marrow cells. Design and Methods. CD34+ cells obtained from three healthy donors were incubated in various combinations of HGF, GM- CSF, and tumor necrosis factor (TNF) for 12 days. Developing cell populations were analyzed for surface markers, morphology and functional capacities by flow cytometry, light microscopy and mixed lymphocyte reaction, respectively. Results. Incubation with HGF alone generated greater number of dendritic cells from CD34+ bone marrow cells than incubation with GM-CSF, or a combination of GM-CSF with TNF. HGF was also found to potentiate the effect of GM-CSF on DC and monocyte development. The effects of HGF were inhibited by the concurrent use of TNF. Interpretation and Conclusions. HGF appears to be a significant factor in the development of dendritic cells from CD34+ bone marrow cells. (C) 2000, Ferrata Storti Foundation.
Keywords: Bone marrow; Dendritic cells; Granulocyte-macrophage colony stimulating factor; Hepatocyte growth factor; Tumor necrosis factor CD34